KEMAMPUAN MENENTUKAN EKSPRESI RELIGI ISLAM DALAM CERPEN HIJRAHMU INSPIRASI DUNIA KARYA WULAN CITRA DEWI SISWA KELAS XI MADRASAH ALIYAH DARUL HIKMAH PEKANBARU - Joni Hidayat; Abdul Razak; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study titled ability to determine the expression of Islamic religion in the world inspirational stories hijrahmu work Citra Dewi Wulan Madrasah Aliyah class XI student of Darul Hikmah Pekanbaru. This research focused on the ability to determine the expression of Islamic religion in the world inspirational stories hijrahmu Citra Dewi Wulan work and to describe a significant difference in Madrasah Aliyah class XI student of Darul hikmah Pekanbaru. The method used is an inferential statistical descriptive method. These research data are the result of the test determines the ability of Islamic religious expression in the work world inspirational stories hijrahmu Citra Dewi Wulan Madrasah Aliyah class XI student of Darul Hikmah Pekanbaru, consisting of 5 lessons with a population of 107 students and the number of samples of 85 students. Based on research, the result that (1) the ability to determine the expression of Islamic religion in the world inspirational stories hijrahmu Citra Dewi Wulan category work is very low; (2) the ability to determine the expression of Islamic religion in the world inspirational stories hijrahmu between the same class, meaning, there is no difference in the ability to determine the expression of Islamic religion in the world inspirational stories hijrahmu Citra Dewi Wulan work under different classes XI or XI. All in all, it can be concluded that the ability to determine the expression of Islamic religion in the world inspirational stories hijrahmu work Citra Dewi Wulan Madrasah Aliyah class XI student of Darul Hikmah category Pekanbaru very low at <60.Keywords: The ability to indicate, Islamic religious expression, inspiration hijrahmuworld short story.